2001
DOI: 10.1080/03079450120054659
|View full text |Cite
|
Sign up to set email alerts
|

The use of serotype 1- and serotype 3-specific polymerase chain reaction for the detection of Marek's disease virus in chickens

Abstract: A serotype 1- and serotype 3-specific detection of Marek's disease virus (MDV) by polymerase chain reaction (PCR) was developed. The sensitivity of the method when applied to cell culture grown virus was comparable with that of cultivation. The method was applied to various tissue samples from chickens experimentally inoculated with serotype 1 or serotype 3 MDV.The serotype 1 strains CVI988 and RB-1B could be detected in feather follicle epithelium up to 56 and 84 days post-inoculation (p.i.), respectively, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
58
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 11 publications
5
58
0
3
Order By: Relevance
“…The ALV-J and ALV-A (Smith et al, 1998), MDV (Handberg et al, 2001) and REV (Wei et al, 2012), were performed, respectively. Primers were utilized in a 25 μL reaction containing 12.5 μL of Emerald Amp Max PCR Master Mix (Takara, Japan), 1 μL of each primer of 20 pmol concentrations, 4.5 μL of water and 6 μL of DNA template.…”
Section: Primers and Pcr Amplificationmentioning
confidence: 99%
“…The ALV-J and ALV-A (Smith et al, 1998), MDV (Handberg et al, 2001) and REV (Wei et al, 2012), were performed, respectively. Primers were utilized in a 25 μL reaction containing 12.5 μL of Emerald Amp Max PCR Master Mix (Takara, Japan), 1 μL of each primer of 20 pmol concentrations, 4.5 μL of water and 6 μL of DNA template.…”
Section: Primers and Pcr Amplificationmentioning
confidence: 99%
“…The authors suggested that the low level of gene expression of ALV-J in the bursa might help to explain the inability of ALV-J to induce lymphoid leukosis. Handberg et al (2001) have developed two PCRs, one specific for type 1 herpesviruses (pathogenic, oncogenic Marek's disease virus (MDV-1)), the other for type 3 avian herpesvirus (herpesvirus of turkeys, often used as a vaccine against Marek's disease). They were particularly interested in developing protocols for the detection and differentiation of these viruses that would be convenient for people collecting material in the field.…”
Section: Avian Leukosis Virusesmentioning
confidence: 99%
“…Virus isolation is usually by virus propagation in cell culture and identificatio n/quantification by cytopathic changes (plaque formation) or identificatio n of infected cells by immunostaining (De Laney et al, 1998). Polymerase chain reaction (PCR) has emerged in recent years as an additional diagnostic tool offering the advantages of serotype specificity (Davidson et al, 1995;Walkden-Brown et al, 2001) and the ability to differentiate between vaccinal and field strains of MDV serotype-1 (Silva, 1992;Zhu et al, 1992;Handberg et al, 2001).…”
Section: Introductionmentioning
confidence: 99%